INFECTIONS IN SPORT - Yanti, Nadchar Anti (Journal of Sports Science and Health, 2019)
Nowadays, “Sport” is a great way to improve physical performance. Many people in the world love sports. They improve themselves to become a sportsman (athletes) and participate in sports events and competitions. Sport injuries among sportsman always occur due to accidents, overuse injuries and infections in sports. There are several ways that sportsman is at risk of infections, ranging from touching holding and physical contact with microorganisms (bacteria, virus, fungi and parasite). First, direct transmission which is consisted of skin-to-skin contact, blood borne transmission and droplet transmission. These routes often occur in situations in which sportsman live in crowded environments as sports camps and competitive events. Moreover, sport training and competition lead them to congregate in the sport club and also share in environments together which can result in the spread of infectious diseases easily. Direct contact transmission through skin-to-skin contact plays a role in the most of infected problem in sport such as bacterial and fungal infections. Tinea pedis (TP) and Tinea corporis are among general fungal skin infected disease that usually found in warm and moist environment. Blood borne infection such as Hepatitis B and C virus often occur due to exposure injured skin or mucous membrane and also was transmitted through blood doping, drug abuse and sexual intercourse. Droplet transmission spreads include sneezing, coughing, or even talking such as pertussis. For indirect transmission, it consists of airborne, vehicleborne and vectorborne transmission. Different type of sports allow the participants expose to contaminated water such as Leptospira bacteria in river or anopheles mosquito in wild, where a competition was established. Conclusion Athlete, trainer and coach should review their knowledge about infectious diseases including proper hygiene to reduce the incidence of the infectious diseases in athletes.